(untitled) (Balthazar, 2023)
When faced with E. Hemingway’s «Hills Like White Elephants», one cannot but be intrigued by the interpretation task required from the reader: the author omits fundamental information, threatening the understanding of the scene described in the text. This article questions, therefore, what it means to interpret this text, discussing the pervasive idea that interpreting always coincides with the answer to the question "what did the author mean?". Critically developing this point, I will thus affirm that a story such by Hemingway will not only determine a new and more pregnant concept of "interpretation" but will also coincide with the demand for a particular narrative involvement of the reader in the story itself.